Understanding Social Isolation Among Urban Aging Adults: Informing Occupation-Based Approaches. (October 2017) - Hand, Carri; Retrum, Jessica; Ware, George; Iwasaki, Patricia; Moaalii, Gabe; Main, Deborah S.
Socially isolated aging adults are at risk of poor health and well-being. Occupational therapy can help address this issue; however, information is needed to guide such work. National surveys characterize social isolation in populations of aging adults but fail to provide meaningful information at a community level. The objective of this study is to describe multiple dimensions of social isolation and related factors among aging adults in diverse urban neighborhoods. Community-based participatory research involving a door-to-door survey of adults 50 years and older was used. Participants ( N = 161) reported social isolation in terms of small social networks (24%) and wanting more social engagement (43%). Participants aged 50 to 64 years reported the highest levels of isolation in most dimensions. Low income, poor health, lack of transportation, and infrequent information access appeared linked to social isolation. Occupational therapists can address social isolation in similar urban communities through policy and practice that facilitate social engagement and network building.